The Influence of School Leadership Behavior and Teacher Work Ethics on Teacher Performance in Private Vocational Schools, Air Kumbang District - Samsuri; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine and describe the influence of principal leadership behavior and teacher work ethic on teacher performance in public elementary schools in Air Kumbang district. With quantitative research methods. The method used is descriptive quantitative method used to process data characteristics related to the average number, look for percentages, and present interesting, easy-to-read data. Data in the form of a questionnaire is classified as quantitative data. The technique of collecting data in this research is through a questionnaire. The results showed that; (1) there is an influence of principal leadership behavior on teacher performance (2) there is an influence between work ethic on teacher performance. (3) there is an influence between the principal's leadership behavior and work ethic together on teacher performance. These findings provide evidence that an increase in principal leadership behavior and work ethic will have an impact on improving the performance of SD Negeri Air Kumbang District teachers.